Liquid biopsies and minimal residual disease in myeloid malignancies - Allam, Sabine; Nasr, Kristina; Khalid, Farhan; Shah, Zunairah; Khan Suheb, Mahammed Ziauddin; Mulla, Sana; Vikash, Sindhu; Bou Zerdan, Maroun; Anwer, Faiz; Chaulagain, Chakra P. (Frontiers in Oncology, 2023)
Minimal residual disease (MRD) assessment through blood component sampling by liquid biopsies is increasingly being investigated in myeloid malignancies. Blood components then undergo molecular analysis by flow cytometry or sequencing techniques and can be used as a powerful tool for prognostic and predictive purposes in myeloid malignancies. There is evidence and more is evolving about the the quantification and identification of cell-based and gene-based biomarkers in myeloid malignancies to monitor treatment response. MRD based acute myeloid leukemia protocol and clinical trials are currently incorporating liquid biopsy testing and preliminary results are encouraging for potential widespread use in clinic in the near future. MRD monitoring using liquid biopsies are not standard in myelodysplastic syndrome (MDS) but this is an area of active investigation. In the future, liquid biopsies can replace more invasive techniques such as bone marrow biopsies. However, the routine clinical application of these markers remains a concern due to lack of standardization and limited number of studies investigating their specificities. Integrating artificial intelligence (AI) could help simplify the complex interpretation of molecular testing and reduce errors related to operator dependency. Though the field is rapidly evolving, the applicability of MRD testing using liquid biopsy is mostly limited to research setting at this time due to the need for validation, regulatory approval, payer coverage, and cost issues. This review focuses on the types of biomarkers, most recent research exploring MRD and liquid biopsy in myeloid malignancies, ongoing clinical trials, and the future of liquid biopsies in the setting of AI.